El papel de El Espectador en la generación de un control político efectivo = The role of El Espectador in the generation of effective political control (2017)
This article explains the role played by El Espectador in relation to the phenomenon of corruption. the phenomenon of corruption. A rigorous follow-up and analysis was carried out and analysis of the news pieces related to the topic, which were published in reaction to the anti-corruption reaction to the anti-corruption campaign led by the Green Party. These pieces were classified in light of content quality standards, and the way in which the framing was given to the media audience. The theoretical The theoretical framework addresses the possible role of the media in the configuration of a deliberative public opinion. deliberative public opinion